Blind data detection and channel estimation for CDMA systems over fading channels - Yu, Qian (2008)
Code-division multiple access (CDMA) technology is attractive as a popular multiple access scheme for personal, cellular and satellite communication services. Direct-sequence CDMA (DS-CDMA) is the most popular CDMA technique, which has been proposed for cellular telecommunication services due to numerous advantages over time-division multiple access and frequency-division multiple access. This thesis is concerned with DS-CDMA systems operating over flat fading channel, frequency-selective fading channel with white Gaussian background noise. This thesis deals with the problem of the channel estimation and multiuser detection for the DS-CDMA system over the fading channels. Several methods are developed for both cases of the flat fading channels and frequency-selective fading channels in order to improve the performance and/or reduce the computational complexity of the multiuser detection.